PENGARUH MODEL PEMBELAJARAN PETAK UMPET TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMPN 18 PEKANBARU KECAMATAN SENAPELAN KOTA PEKANBARU - Amina, Siti; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research background was related to the lack of motivation to learn PPKn on 8th grade students at SMPN 18 Senapelan Pekanbaru kecamatan senapelan kota Pekanbaru. The problem formulation is: “is there any effect on the use of hide and seek learning model toward students’ learning motivation?”. This study aims to determine the effect of hide and seek learning model upon learners’ motivation. Using experimental research with descriptive-qualitative approach, the sample was taken based on the "Random Sampling" technique. VIII D class as an experimental class were applied hide and seek learning model, while VIII A as the control class which used conventional methods. Homogeneity test, t-test and gain test were used to analyze the data. The results showed that there was a difference percentage on students’ motivation level between two classes (tcount=39,48> ttable=1,99). The average learning motivation on experimental class was from 21.42 to 27.22 while the average learning motivation of PPKn in the control class was from 21.97 to 22.66. With contributions as much as 0.5 included in the category of "medium", thus there is an effect of using hide and seek learning model and conventional learning model towards student’s learning motivation to learn PPKn in SMP 18 Senapelan, Pekanbaru .Keywords: Hide and Seek, Learning Motivation